Length-weight relationship, condition factor, and reproductive biology of the bigeye thresher Alopias superciliosus in Southern Java, Indonesia - MUHAMMAD ARIF RAHMAN; LEDHYANE IKA HARLYAN; ABU BAKAR SAMBAH; ARIEF SETYANTO; ALYAA FARAH QONITAH; MIFTAH WISNU PURNOMO AJI; ERLYN YULIANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rahman MA, Harlyan LI, Sambah AB, Setyanto A, Qonitah AF, Aji MWP, Yulianti E. 2025. Length-weight relationship, condition factor, and reproductive biology of the bigeye thresher Alopias superciliosus in Southern Java, Indonesia. Biodiversitas 26: 2557-2564. The bigeye thresher shark Alopias superciliosus is one of two known Alopiidae species lived in Indonesian waters. This species was usually captured in southern waters of Indonesia (Indian Ocean) by various fishing gears. This study aims to investigate size structure, length-weight relationships, relative condition factor, and length at first maturity of A. superciliosus landed at Cilacap Ocean Fishing Port, Central Java, Indonesia, providing data for sustainable management. Sampling was conducted monthly over seven months, documenting fork length, body weight, and identifying sex through external examination from 484 sharks (241 males and 243 females). Results revealed a wide size range (77-256 cmFL) of samples and a balanced overall sex ratio, although monthly fluctuations were observed. Growth pattern was negative allometric with value of b: 2.871, 2.789, and 2.936 for combined sex, males, and female, respectively. Relative condition factor predominantly exceeded 1.00. The length at first maturity for males was 150.61 cm, with around 40% of sampled individuals caught prior to sexual maturity. These results underscore the vulnerability of A. superciliosus populations and highlight the urgent need for management measures such as size-limit regulations and modifications of fishing operations to reduce bycatch. Overall, this study provides crucial baseline data for policymakers, laying the groundwork for more effective conservation of bigeye thresher sharks in Indonesian waters and beyond.